Spectrophotometric Determination of Gatifloxacin - Jane, Jacob.; Subrahmanyam, E.V.S.; Sathyanarayana, D. (Asian Journal of Chemistry, 2010)
A simple and sensitive method was developed for the determination of gatifloxacin in pureand dosage form. The method was based on the oxidative coupling reaction of gatifloxacinwith 3-methyl-2-benzothiazolinone hydrazone in the presence of an oxidizing agent like cericammonium sulphate. The chromogen attained a green colour and exhibited absorptionmaxima at 630 nm. Good agreement with Beer's law was found in the range of 2-10 μg/mL.The method did not require any separation of soluble excipients in the formulation. Theresults obtained are reproducible with coefficient of variation less than 1.0%.